ΔFosB regulates rosiglitazone‐induced milk fat synthesis and cell survival. Issue 12 (26th June 2018) - Wei, Xuefeng; Li, Hui; Zhao, Guangwei; Yang, Jiameng; Li, Lihui; Huang, Yongzhen; Lan, Xianyong; Ma, Yun; Hu, Linyong; Zheng, Huiling; Chen, Hong
Abstract : Rosiglitazone induces adipogenesis in adipocyte and regulates cell survival and differentiation in number of cell types. However, whether PPARγ regulates the synthesis of milk fat and cell survival in goat mammary gland remains unknown. Rosiglitazone strongly enhanced cellular triacylglycerol content and accumulation of lipid droplet in goat mammary epithelial cells (GMEC). Furthermore, ΔFosB decreased the expression of PPARγ at both mRNA and protein levels, and rosiglitazone‐induced milk fat synthesis was abolished by ΔFosB overexpression. ΔFosB reduced milk fat synthesis and enhanced saturated fatty acid concentration. Rosiglitazone increased the number of GMEC in G0/G1 phase and inhibited cell proliferation, and these effects were improved by overexpression of ΔFosB. ΔFosB was found to promote the expression of Bcl‐2 and suppress the expression of Bax, and protected GMEC from apoptosis induced by rosiglitazone. Intracellular calcium trafficking assay revealed that rosiglitazone markedly increased intracellular calcium concentration. ΔFosB protected GMEC from apoptosis induced by intracellular Ca 2+ overload. ΔFosB increased MMP‐9 gelatinolytic activity. SB‐3CT, an MMP‐9 inhibitor, suppressed the expression of Bcl‐2, and increased intracellular calcium levels, and this effect was abolished by ΔFosB overexpression. SB‐3CT induced GMEC apoptosis and this effect was inhibited by ΔFosB overexpression. These findings suggest that ΔFosB regulates rosiglitazone‐induced milk fat synthesis and cell survival. Therefore, ΔFosB may be an important checkpoint to control milk fat synthesis and cell apoptosis. Abstract : ΔFosB suppresses PPARγ agonist rosiglitazone‐induced cellular lipid‐droplets accumulation and protects cells from PPARγ activated‐induced apoptosis. ΔFosB also increased MMP‐9 gelatinolytic activity, and inhibition of MMP‐9 suppressed the expression of Bcl‐2 and increased intracellular calcium levels, and these effects were improved by overexpression of ΔFosB.